2014
DOI: 10.1126/science.1250463
|View full text |Cite
|
Sign up to set email alerts
|

Statistical binning enables an accurate coalescent-based estimation of the avian tree

Abstract: Gene tree incongruence arising from incomplete lineage sorting (ILS) can reduce the accuracy of concatenation-based estimations of species trees. Although coalescent-based species tree estimation methods can have good accuracy in the presence of ILS, they are sensitive to gene tree estimation error. We propose a pipeline that uses bootstrapping to evaluate whether two genes are likely to have the same tree, then it groups genes into sets using a graph-theoretic optimization and estimates a tree on each subset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
252
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(254 citation statements)
references
References 83 publications
2
252
0
Order By: Relevance
“…Recent statistical advances in coalescent-based methods have indicated that statistically grouping genes into subsets can improve the accuracy of species tree estimation (Mirarab et al 2014). Our analyses also benefited from this approach.…”
Section: Phylogenetics and Taxonomymentioning
confidence: 67%
“…Recent statistical advances in coalescent-based methods have indicated that statistically grouping genes into subsets can improve the accuracy of species tree estimation (Mirarab et al 2014). Our analyses also benefited from this approach.…”
Section: Phylogenetics and Taxonomymentioning
confidence: 67%
“…We further used coalescent-based species tree estimation to test for potentially misleading phylogenetic signal due to incomplete lineage sorting. This analysis was conducted both with individual gene trees and with trees based on alignments binned according to the binning approach of Mirarab et al 55 .…”
Section: Methodsmentioning
confidence: 99%
“…Further, these simulations [86] did not compare the performance of coalescence methods to concatenation in their study of the effects of recombination on coalescence methods. More recently, the idea of concatalescence has been reimagined as statistical binning, in which gene trees and alignments are assigned to a bin based on 'combinability' before creating supergene trees for downstream coalescence analysis [87]. Accurate gene tree reconstructions are also central to the coalescent approach as each tree is given equal weight in the analysis; however, accurate reconstructions become increasingly difficult with decreasing c-gene sizes as more taxa are added to the analysis [19].…”
Section: Morphology Moleculesmentioning
confidence: 99%